Sharia Financial Instruments and Banking Roles in Strengthening Financial Deepening: Instrumen Keuangan Syariah dan Peran Perbankan dalam Menguatkan Pendalaman Keuangan - Rulitasari, Shindy Gresilya; Rahmawati , Imelda Dian (Indonesian Journal of Innovation Studies, 2025)
General Background: Financial deepening serves as an essential indicator of a nation’s financial system maturity, reflecting its ability to channel funds efficiently to drive sustainable economic growth.Specific Background: In Indonesia, the Sharia financial sector—through instruments such as sukuk and Islamic banking—has grown significantly, providing alternative channels for liquidity and capital distribution.Knowledge Gap: Despite this growth, comprehensive empirical studies integrating both Sharia capital market and banking variables in assessing financial deepening remain scarce.Aims: This study investigates the roles of corporate sukuk, state sukuk, third-party funds, and financing from Islamic banks in strengthening financial deepening in Indonesia from 2017 to 2020.Results: Using multiple linear regression analysis, findings indicate that all four variables positively and significantly contribute to financial deepening, demonstrating the vital role of Islamic finance in national liquidity expansion.Novelty: The study integrates dual-sector variables—Sharia capital market and banking—into a unified model, offering a holistic view of Indonesia’s Islamic financial ecosystem.Implications: Results underscore the necessity for policymakers to optimize Sharia-based instruments to improve liquidity, promote financial inclusion, and sustain economic resilience. Highlights: Sharia finance strengthens Indonesia’s financial depth through sukuk and banking. Dual-sector integration provides a broader analytical perspective. Findings guide policy development for sustainable financial systems. Keywords: Islamic Finance, Sukuk, Sharia Banking, Financial Deepening, Indonesia